Understanding the Nexus between Oil Price Volatility and Trade Balance in GCC Countries: A Comparative Investigation of Panel Linear and Nonlinear ARDL Models - Alassaf, Ghazi (International Journal of Energy Economics and Policy, 2024)
In this paper, we re-examine the relationship between oil price volatility and trade balance in oil exporting countries; namely GCC countries over the period 1989-2021. The empirical analysis employs a comparative approach, comparing the results obtained from a panel autoregressive distributed lag (ARDL) model with those from a nonlinear ARDL (NARDL) model. This research contributes to the literature by shedding light on the intricate linkages between energy markets and trade performance in major oil-exporting countries. The motivation stems from the importance of assessing how fluctuations in oil prices, a crucial factor for oil-exporting economies, affect their trade balance dynamics. Our empirical results depict that trade balances of GCC countries respond asymmetrically to changes in oil price although the positive oil price impacts showed greater effects on trade balance as opposed to the negative ones in the short run, the effect was reversed in the medium to long run. The findings reveal that the NARDL model provides a better fit to the data and offers richer insights into the relationship between oil price volatility and trade balances in the GCC region. Specifically, the empirical results indicate that positive oil price volatility has a greater effect on trade balances compared to negative volatility, and the speed of adjustment to equilibrium is faster in the NARDL model results. This asymmetric effect, with positive shocks exhibiting a larger influence, aligns with the expectations for oil-exporting countries. The results from the NARDL model highlight that policymakers need to account for these asymmetries when managing external trade positions in response to oil market fluctuations.